Considering the Juridical and Extra-Juridical Aspects of the Domestic Violence Relief System in Poland - Dutka, Joanna (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The paper explores various problems within the two-track model of domestic violence prevention and relief system in Poland. The two tracks are oriented around social services and criminal courts, respectively. The common problem for both tracks is the shortage of personnel sufficiently trained to deal with the specifics of family abuse. Moreover, the discriminatory attitudes towards the victims are prevailing, while the gender aspect of the problem is poorly recognised in everyday institutional practice. Consequently, the cultural patterns that domestic violence stems from are rarely challenged, undercutting prospective long-term prevention strategies.